Application of Cr(VI) transport across the polymer inclusion membrane with calixresorcin[4]arene derivative as ion carrier. Issue 12 (12th August 2020) - Zawierucha, Iwona; Nowik-Zajac, Anna; Kozlowski, Cezary
ABSTRACT: In this study, the experiments were performed to evaluate the Cr(VI) removal efficiency by transport across the polymer inclusion membrane with calixresorcin[4]arene derivative as ion carrier. The several influence factors such as carrier concentration, the amount of plasticizer in the membrane as well the effect of acid type and its concentration in source phase and the membrane stability were investigated. It was found that the immobilized calixresorcin[4]arene derivative in membranes effectively extracted chromium from acidic media. Under optimized conditions, the Cr(VI) removal efficiency was 98.4%.